2012
DOI: 10.1371/journal.pone.0030959
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Actin Turnover in Retrograde Actin Network Flow in Neuronal Growth Cones

Abstract: The balance of actin filament polymerization and depolymerization maintains a steady state network treadmill in neuronal growth cones essential for motility and guidance. Here we have investigated the connection between depolymerization and treadmilling dynamics. We show that polymerization-competent barbed ends are concentrated at the leading edge and depolymerization is distributed throughout the peripheral domain. We found a high-to-low G-actin gradient between peripheral and central domains. Inhibiting tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
72
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 58 publications
12
72
0
Order By: Relevance
“…Using pharmacological compounds, we showed that both actin polymerization forces and myosin II tension contributed to flow generation. Actin flow was high in the peripheral region, where actin monomers incorporate into new filaments, and slowed down toward the central region, where actin filaments disassemble, consistent with fluorescence speckle microscopy data (2,18,37) and the universal actin cycling model (38,39). An important parameter is the time that a given actin monomer spends in the retrograde flow, which seems to be independent of the flow rate itself.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Using pharmacological compounds, we showed that both actin polymerization forces and myosin II tension contributed to flow generation. Actin flow was high in the peripheral region, where actin monomers incorporate into new filaments, and slowed down toward the central region, where actin filaments disassemble, consistent with fluorescence speckle microscopy data (2,18,37) and the universal actin cycling model (38,39). An important parameter is the time that a given actin monomer spends in the retrograde flow, which seems to be independent of the flow rate itself.…”
Section: Discussionsupporting
confidence: 79%
“…The actin-capping drug cytochalasin D, the monomeric actin-sequestering drug latrunculin A, and the actinstabilizing agent jasplakinolide all dramatically diminished the fraction of rearward-moving actin-mEos2 molecules (21%, 7%, and 2%, respectively) ( Fig. S5), consistent with a major role of actin tread-milling in generating the flow (2,3,5). Myosin-light chain (MLC)-GFP was localized in the intermediary region of the growth cone, and MLC-Eos2 trajectories were mostly confined in this area (Fig.…”
Section: Significancesupporting
confidence: 59%
See 1 more Smart Citation
“…The post-translational modification of F-actin adds an additional level of actin network regulation (reviewed in [69]). The unusually large growth cones of Aplysia bag cell neurons have provided the principal model system for the study of growth cone structure and dynamics [15,[70][71][72][73][74][75][76]. The simultaneous assembly of actin filaments at the growth cone edge and disassembly from pointed filament ends throughout the P-domain generate a continuous actin turnover refered to as 'treadmilling' (Figures 1A and 3A) [3,15].…”
Section: Actin Dynamicsmentioning
confidence: 99%
“…F-actin disassembly is mediated by a collection of actin-binding proteins that can facilitate actinfilament depolymerisation or severing, such as those belonging to the Mical and actin-depolymerising factor (ADF)/cofilin families [78,79]. The actin monomers subsequently generated can then be translocated, either by diffusion or active transport, towards the cell edge and re-incorporated into polymerising filaments, thus completing the actin treadmill [16,65,76]. Polymerising F-actin filaments at the edge of the growth cone, which can be modelled as elastic Brownian ratchets, produce a protrusive force upon the cell membrane [80].…”
Section: Actin Dynamicsmentioning
confidence: 99%